Clinical Presentation of Schnitzler's Syndrome: A Rare Autoimmune Disease - Vishal Patel MD; Darshana Balasubramaniam MD; Vanessa Cavero-Chavez MD; Lyda Cuervo-Pardo MD; Catalina Sanchez-Alvarez MD (SAGE Publishing, 2023)
Schnitzler's Syndrome (SS) is a rare late-onset acquired autoinflammatory disorder which consists of chronic urticaria associated with a monoclonal IgM-kappa gammopathy, arthralgias, skeletal hyperostosis, lymphadenopathy, and recurrent constitutional symptoms. The average age of diagnosis is 51 years with a slight male predominance with a male to female ratio of 1.6. Diagnosis of SS requires the presence of 2 major criteria including chronic urticaria and monoclonal IgM along with at least two of the following minor criteria: recurrent intermittent fevers, bone pain, arthralgias, elevated erythrocyte sedimentation rate (ESR), neutrophilic dermal infiltrate on skin biopsy, and leukocytosis or elevated C-reactive protein (CRP). Early diagnosis and clinical awareness are paramount in SS as it is associated with a 15-20% risk of lymphoproliferative malignancy. The median overall survival is 12.8 years. We present a case of a 39-year-old female with new onset urticaria associated with recurrent fevers and joint pain. Symptoms were refractory to steroids, and high dose antihistamines. Multi-disciplinary evaluation resulted in the ultimate diagnosis of Schnitzler's Syndrome. The patient was ultimately treated with canakinumab (Il-1 inhibitor), with near resolution of symptoms. This case demonstrates the importance of a broad differential diagnosis and maintaining a high clinical suspicion for rare diseases when presented with a complex form of an otherwise common condition.